Applications of the Reversible Boronic Acids/Boronate Switch to Nucleic Acids. Issue 8 (31st May 2022) - Debiais, Mégane; Vasseur, Jean‐Jacques; Smietana, Michael
Abstract: Over the last decades, boron and nucleic acids chemistries have gained a lot of attention for biological, medicinal and analytical applications. Our laboratory has a long‐standing interest in both chemistries and owing to the ability of boronic acids to react with cis ‐diol function in aqueous media we developed over the years a variety of applications ranging from molecular recognition and sensing to the development of reversible dynamic systems in which the natural phosphodiester linkage was replaced by a boronate. In this account, we summarize research results from our group from our preliminary studies on molecular recognition of ribonucleosides to the dynamic assembly of functional DNAzymes. In particular, the various parameters influencing the dynamic nature of these reversible covalent bonds able to respond to external stimuli are discussed. Finally, current challenges and opportunities for boron‐based nucleic acids are also addressed. Abstract : This personal account summarizes the research carried out in our laboratory at the crossroads of nucleic acids and boronic acids chemistries.